Statistics and Economy of Fish Farming in Ukraine - Popova О. L. (Statistics of Ukraine, 2017)
Pisciculture of Ukraine, according to the head of the State Agency of Fisheries, is being reformed. At the same time, it is estimated that 60-70% of the fish industry is “in the shade”. Therefore, reliable information is needed, first of all - official statistics on the fish industry development in the country, which would be in line with European approaches. Being recognized as a separate area of economic activity to supply important food products for the population through their extraction from reservoirs, the fish industry should be represented by official statistics in the range of indicators provided for agricultural products. The purpose of the article is to reveal the results of the analysis of existing statistics on the extraction of water bioresources, with an accent on problem aspects, as well as developing proposals for improving the economic bloc of domestic statistics in this economic activity area. On the basis of the analysis of the available official statistic on the extraction of aquatic biological resources, including aquaculture, the problematic aspects of the economic block of indicators in the industry - costs and prices, are defined. It is also emphasized that both general and regional data on the number of business entities and water area are not available. Since 2016 official statistical information on the production of aquaculture is not provided, although earlier it was submitted in the thematic statistical collection; Administrative reports are now provided, but with all possible encumbrances. The proposals for improving the economic statistics on pisciculture are substantiated. A review of available statistics on the development of the pisciculture in Ukraine is provided. The comparative analysis of data by various forms of statistical reports, allowed to identify the problematic aspects of sectoral statistics Based on the results of the analysis, the proposals are maid to improve the economic statistics of the pisciculture in Ukraine. Taking into account the sectoral and statistical proposal will contribute to the formation of reliable data and transparency of this sector; allow to defend the need for its state support as an important part of the national economy